Mengatasi Hambatan Belajar IPA di SD: Fokus pada Kemampuan Abstraksi dan Hubungan Sebab-Akibat - Ika Putra Viratama; Alifia Nida Safira Meidiah; Isrowiyah Isrowiyah; Al Dewiyana Muhammad Idris; Jumalia Taliba (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Science lessons in primary school significantly contribute to the early development of logical, scientific and systematic reasoning skills. However, learning science can be challenging, especially when it comes to understanding abstract concepts and cause-and-effect interactions. This is due to the fact that, as per Piaget's theory, primary school students are still in the concrete operational stage and have limited cognitive growth. Data regarding abstraction ability and causal reasoning in the context of science education were collected from various scientific sources using the literature review research methodology. According to the research findings, STEAM integration, project-based learning strategies such as Project Based Learning (PBL), and the use of real and visual aids can help lower learning barriers. Successful learning is also influenced by the teacher's role as facilitator, which involves presenting the material in a relevant and contextualized way and fostering a positive learning environment. Real-world examples and exceptional examples, such as the use of worksheets based on cause-and-effect relationships and basic experiments, demonstrate how useful these strategies are for improving abstract thinking and understanding of cause-and-effect relationships. Developing innovative teaching methods based on practical, exploratory and integrative experiments is essential for maximizing the scientific understanding of primary school students.